2008
DOI: 10.2320/matertrans.mra2008213
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction of Mn(II) from Strong Hydrochloric Acid Solutions by Alamine336

Abstract: Solvent extraction reaction of Mn(II) by Alamine336 from strong HCl solution up to 10 kmol/m 3 was identified from the experimental data by using slope analysis method. The equilibrium constant for this solvent extraction reaction was estimated by considering the complex formation reactions between Mn(II) and chloride ion. The activity coefficients of solutes present in the aqueous phase were calculated by Bromley equation. The necessary thermodynamic parameters for the formation of MnCl þ were evaluated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…31 P NMR spectra of P 8,8,8,12 Cl and P 8,8,8,12 R 2 POO both exhibited a singlet at around 34.5 ppm, as shown in Figure2. This signal was attributed to the quaternary phosphorus atom of P 8,8,8,12[18,25].…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…31 P NMR spectra of P 8,8,8,12 Cl and P 8,8,8,12 R 2 POO both exhibited a singlet at around 34.5 ppm, as shown in Figure2. This signal was attributed to the quaternary phosphorus atom of P 8,8,8,12[18,25].…”
mentioning
confidence: 86%
“…that occurred during the extraction process. As shown in the31 P NMR spectrum of P 8,8,8,12 R 2 POO in Figure 2d, the content of bis(2,4,4-trimethylpenthyl)phosphinic acid, which is present at 47.4 ppm decreased after adding excess Figure 2. 31 P NMR spectra of (a) P 8,8,8,12 Cl, (b) P 8,8,8,12 R 2 POO, (c) P 8,8,8,12 R 2 POO after extraction, and (d) P 8,8,8,12 R 2 POO after NaOH treatment.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In this estimation of equilibrium constant, the activity coefficients of species in the aqueous phase are calculated by applying the Bromley equation and the complex formation reactions between manganese and chloride ions. 10 Sousa Junior et al reported the equilibrium constant for the solvent extraction of manganese from sulfate solutions with D2EHPA in isoparaffin. The modified Davies equation was applied for the calculation of activity coefficients of all solutes in the aqueous phase.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lee and Filiz calculated the extraction equilibrium constant for the solvent extraction reaction of Mn(II) from hydrochloric acid solutions with Alamine 336. In this estimation of equilibrium constant, the activity coefficients of species in the aqueous phase are calculated by applying the Bromley equation and the complex formation reactions between manganese and chloride ions . Sousa Junior et al reported the equilibrium constant for the solvent extraction of manganese from sulfate solutions with D2EHPA in isoparaffin.…”
Section: Introductionmentioning
confidence: 99%